A novel no-latency simple-to-implement sender-based packet-loss recovery technique for multimedia streams - Rahnama, Behnam; Elci, Atilla (IEEE, 2006)
We consider recovery techniques for packet-loss in the multimedia streams at both sender- and receiver-sides. We investigate recovery techniques as bases of useless packet transmission avoidance in order to release bandwidth by avoiding sending unintelligible packets. At times, packet-loss exceeds a given threshold such that recovery techniques are not able to cope with packet-losses. Therefore, algorithms supplying lower latency and higher degree of recovery are needed. Moreover, faster algorithms for generating packets, transmitting, and recovering from losses in the streams, help managing unintelligible flow for the various multimedia streams. Here, we propose the Fast Forward Algorithm (FFA) that removes latency in packet generation, is practical, and is very simple to implement. FFA is equally suitable for interactive and non-interactive applications. Simulation is used to show that FFA is superior to other interleaving methods.
7th International Symposium on Computer Networks -- JUN 16-18, 2006 -- Istanbul, TURKEY
Keywords: Transmission; Networks